2018
DOI: 10.1111/jfs.12553
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Listeria monocytogenes growth on vacuum packaged rainbow trout (Oncorhynchus mykiss) with carvacrol and eugenol

Abstract: The aim of this study was to evaluate the effects of carvacrol and eugenol, separately and in combination, on survival of Listeria monocytogenes, and sensory and microbiological characteristics in vacuum packaged Oncorhynchus mykiss during refrigerated storage (4 ± 1 °C) for 20 days. The control fish fillets were analyzed for microbial (total mesophilic and psychrotrophic bacteria and lactic acid bacteria) and sensory properties. Fish fillets treated with carvacrol, eugenol, and their combination displayed pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Eugenol could prolong the shelf life of seabass samples because of its remarkable inhibitory effect. Dimitrijević et al [30] also demonstrated that eugenol showed good antimicrobial activity on retarding TVC growth, similar results also shown towards the increase of H 2 S-producing bacteria, Pseudomonas spp., and psychrophile in the current research. H 2 S-producing bacteria is one of the specific spoilage organisms in seabass samples during cold storage [31].…”
Section: Microbiological Resultsmentioning
confidence: 66%
“…Eugenol could prolong the shelf life of seabass samples because of its remarkable inhibitory effect. Dimitrijević et al [30] also demonstrated that eugenol showed good antimicrobial activity on retarding TVC growth, similar results also shown towards the increase of H 2 S-producing bacteria, Pseudomonas spp., and psychrophile in the current research. H 2 S-producing bacteria is one of the specific spoilage organisms in seabass samples during cold storage [31].…”
Section: Microbiological Resultsmentioning
confidence: 66%
“…Listeria monocytogenes in seabream fillets packaged in 60 to 80% CO 2 and 40 to 20% N 2 was reduced by 1.5 log CFU/g after 16 days of storage at 0 °C, compared with an over 2 log CFU/g increase in air‐packaged fillets stored at 4 °C (Provincial et al., 2013). The L. monocytogenes population in vacuum‐packaged rainbow trout fillets decreased from 4.48 to 3.13 log CFU/g during storage at 4 °C for 20 days (Dimitrijevic et al., 2019).…”
Section: Microbiological Safety Of Fish and Fish Productsmentioning
confidence: 99%
“…The lower O 2 could inhibit the growth of aerobic spoilage bacteria and the decomposition of trimethylamine oxide (TMAO) into trimethylamine, which can form a strong antimicrobial barrier with high CO 2 . Furthermore, eugenol possesses "moderate-strong inhibitory" characteristics to inhibit the microbial growth to extend the shelf-life of fish during storage [28,29]. Compared with AP treated sea bass samples, the gelatin active coating containing eugenol and MAP treated samples significantly inhibited the microbial growth during superchilling storage at −0.9 • C. Marchese et al [30] reported that eugenol showed a good antimicrobial effect on Gram-negative bacteria.…”
Section: Introductionmentioning
confidence: 99%